Toward eco-friendly fertilizers: modulating nutrient release from biopolyurethane coatings by adjusting isocyanate index and polyol percentage - Md Sam, Nor Syahidah; Krishnen, Ganisan; Baharulrazi, Norfhairna; Abdullah, Luqman Chuah; Majid, Rohah A. (John Wiley and Sons, 2025)
The global demand for sustainable agricultural practices necessitates the development of eco-friendly slow-release fertilizers (SRFs). This study investigates biopolyurethane-coated urea (BPUC) as a promising SRF material, focusing on the effects of NCO/OH ratio and castor oil (CO) and polycaprolactone (PCL) blending percentage in the polyol phase on biopolyurethane films (BPUF) physicochemical properties and BPUC’s nutrient release performance. BPUC was prepared using a solvent-free, green synthesis method, with variations in NCO/OH ratios (1.0–2.0) and PCL blending percentages (10%–40%). Key properties, including crosslink density, glass transition temperature, mechanical strength, biodegradability, and nutrient release behavior, were systematically characterized. The results reveal that increasing the NCO/OH ratio and PCL content enhances crosslink density (up to 7.463 × 10−3 mol/cm3) and tensile strength, reducing nutrient diffusion and extending release longevity to 48.5 days. The findings demonstrate the tunability of BPUC coatings to achieve desired release profiles, highlighting the strong correlation between microstructural properties and nutrient release kinetics. These findings suggest that tailoring the NCO/OH and polyol ratios in BPUC can effectively meet the nutrient release needs of crops while reducing environmental impact. This approach highlights a promising, eco-friendly alternative for developing sustainable, controlled-release fertilizers.